Howkan - Adelaide de Menil (1966)
Adelaide de Menil, in communication with Bill Reid, traveled the Northwest Coast from Vancouver Island to Southeast Alaska photographing the monumental art of Coastal First Nations. Many of the images she captured show totem poles, and architecture in the final stages of decay before returning to the forest. The title of these images reflect the date that they were taken, and the roll and frame number assigned by Ms. de Menil.